Effects of Additives on Structural and Optical Properties of Selenium Thin Films - Singh, Harpreet (International Journal of Computer Sciences and Engineering, 2019)
Chalcogenide alloys are highly explored due to their various technological applications. In present study, effect of additives on structural and optical properties of a-Se thin films is observed. Bulk samples of a-Se, In50Se50 (InSe) and Sb50Se50 (SbSe) are prepared using melt quench technique. Thin films of powdered samples have been deposited by thermal evaporation technique. X-ray diffraction study reveals that Se and SbSe thin films are amorphous in nature, whereas InSe thin films are crystalline in nature which indicates about phase change upon In incorporation. The change in morphology due to phase change, studied by field emission scanning electron microscopic image, is also shown. The optical transmission is also found to vary with Sb and In alloying. The optical band gap decreases greatly in SbSe with slight decrease in transmission, whereas in InSe, transmission reduced drastically with decrease in band gap. The decrease in transmission in InSe is attributed to the phase change in InSe thin films. The tuning of band gap and transmission upon In and Sb addition makes them applicable for various technological applications.